Ameliorating effects of biochar on photosynthetic efficiency and antioxidant defence of Phragmites karka under drought stress. (12th January 2020) - Abideen, Z.; Koyro, H.‐W.; Huchzermeyer, B.; Ansari, R.; Zulfiqar, F.; Gul, B.
Abstract: Biochar (BC) has been reported to improve growth and drought resistance in many plants. However, adequate information on the drought resistance mechanism mediated of BC on Phragmites karka, a bioenergy plant, is not available. The impact of BC addition (0%, 0.75% and 2.5%) on plant growth and physiology of P. karka under drought was assessed. Soil water‐holding capacity and soil water content were significantly improved with 0.75% BC as compared with the un‐amended controls. This resulted in improved plant performance under drought conditions. An increase of parameters, such as plant fresh and dry biomass, root to shoot ratio and root mass fraction, was paralleled by an increase of chlorophyll content, net photosynthesis rate and water use efficiency of plants. Plants treated with 0.75% BC experienced less oxidative stress due to higher photosystem II efficiency and stimulated activity of antioxidant defense systems. Our results demonstrate that soil amendment with 0.75% BC allow the potential energy plant P. karka to grow in an arid habitat. Abstract : Biochar improves plant‐soil interaction, growth, net photosynthesis as well as ROS stress‐relieve under drought by the antioxidant defense system of Phragmites karka .